Renoprotective effects of Cucumeropsis mannii seed oil on cisplatin-induced nephrotoxicity in Wistar rats - Boniface Anthony Ale; Patrick Maduabuchi Aja; Ikechukwu Jacob Okoro; Felix Emmanuel Nwite; Peter Chinedu Agu; Ejike Daniel Eze; Vitus Ikenna Nnamani; Victor Nwadiogbu Ogugua (Elsevier, 2024)
Background: The growing prevalence of cancer and the concomitant rise in chemotherapy use have led to an increased incidence of kidney-related diseases, including nephrotoxicity. Cisplatin (CP) is a widely used and potent anticancer drug, but nephrotoxicity limits its clinical application. Purpose: Our study aimed to determine the phytochemicals and median lethal dose of Cucumeropsis mannii seed oil (CMSO) using standard methods and to further investigate the effects of CMSO on CP-induced nephrotoxicity in male Wistar rats. Methods: Twenty-one rats (100 to 150 g) were randomly divided into seven groups (n = 3) and treated with CMSO or normal saline for ten days. Group A received 1.0 mL of normal saline, irrespective of the body weight (b.w.). Groups B-D received 2500, 5000, and 7500 mg/kg b.w., respectively, of the CMSO and a single intraperitoneal dose of CP (8 mg/kg) on the seventh day. Groups E and F were administered 2500 mg/kg and 7500 mg/kg b.w., respectively, of the CMSO without CP administration. Group G received a single intraperitoneal dose (8 mg/kg b.w.) of CP on the seventh day without CMSO treatment. Results: The analysis of CMSO revealed the presence of various phytochemicals such as hydrogen cyanide, glycosides, saponins, steroids, tannins, alkaloids, terpenoids, phenols, and flavonoids. Acute toxicity testing demonstrated the safety of CMSO up to 5000 mg/kg b.w. We discovered that the CP administration increased serum creatinine (sCr), urea, blood urea nitrogen (BUN), and malondialdehyde (MDA) levels in rats and markedly decreased renal superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) activities and glutathione (GSH) levels. CMSO attenuated kidney dysfunction, oxidative stress, and lipid peroxidation. Interestingly, CMSO prominently decreased sCr, urea, and BUN levels, boosted the activity of SOD, CAT, and GPx, increased GSH levels, and significantly (p < 0.05) decreased MDA levels. Histological assessment corroborated these biochemical findings. Conclusion: Our findings highlight the potential of CMSO as a protective agent against CP-induced nephrotoxicity. The observed effects are attributable to the rich phenolic and flavonoid content of CMSO. These findings have significant implications for developing complementary therapies to mitigate chemotherapy-associated kidney damage, potentially enhancing the safety and efficacy of cisplatin-based cancer treatments. Further investigation is needed to explore the clinical applications of CMSO for cancer patients.